Cognitive therapeutic exercise in early proprioception recovery after knee osteoarthritis surgery - Ma, Yubao; Fan, Zhijiao; Gao, Weiguang; Yu, Zihan; Ren, Muchen; Ma, Quansheng; Song, Dejun; Zhang, Lihua; Mi, Lixin (Frontiers in Rehabilitation Sciences, 2022)
Objective This research aims to explore the therapeutic effect of cognitive therapeutic exercise (CTE) in proprioception recovery after knee osteoarthritis (KOA) surgery. Methods In total, thirty-seven patients recovering from KOA surgery (including 27 patients who had undergone high-tibial osteotomy (HTO) procedure and 10 patients who had received total knee arthroplasty (TKA) treatment were randomly assigned to two groups: 18 patients in the CTE group and 19 patients for the control group (non-CTE). Patients in the CTE group received proprioceptive training as cognitive therapy to facilitate proprioception recovery for up to 4 weeks: 5 days a week and two 10-min sessions a day. Except for cognitive therapeutic exercise, the NCTE group and CTE group had the same treatment protocols. All the interventions began with permission from the surgeon-in-charge. In this research, we applied the joint repositioning training or joint-matching tasks, which is part of the proprioceptive training as a measurement for a proprioceptive training result where patients moved their knee joint from 0° (completely straight knee joint) to produce a presented joint angle, such as 30, 60, and 90° of flexion. Joint-matching task results were recorded before the treatment, at 2 and 4 weeks, postoperatively. The absolute difference between the results of these exercises and the knee flexion angle targets will be measured at each test—pre-rehabilitation (Pre-Reha), 2 weeks post-rehabilitation (2 weeks post-Reha), and 4 weeks post-rehabilitation (4 weeks post-Reha). Results The absolute difference in the CTE group was significantly smaller than that of the control group after 4 weeks of treatment (P < 0.05). After 2 weeks of cognitive therapeutic exercise, the absolute difference between patients' exercises of joint repositioning and the target angle of 30° in the CTE group was smaller than that of the NCTE group (P < 0.01). After 4 weeks of therapy, the joint position sense (JPS) among patients who received cognitive therapeutic exercise when performing joint repositioning at angles of 30 and 60° were better improved than those without receiving proprioceptive training with the absolute difference smaller than those of the control group (P < 0.05). Conclusion The joint reposition training provided for the CTE group is a painless proprioceptive training practice. This method is simple and effective, making it easy for patients to understand the purpose of training and improve patient engagement. The research showed that after 4 weeks of rehabilitation and physical training, the proprioception sense of both the NCTE and CTE groups improved significantly, and the efficacy of proprioceptive training in the CTE group was better than that of the NCTE group, which provided a new approach to the early proprioception recovery of a patient with KOA after surgery.